Implementation Of Legged Robot Control With Pixy Camera Module Through Image Processing Technique - alfhadila fhadil (Politeknik Negeri Padang, 2026)
This tool is the development and implementation of a robot control system using the Pixy camera module through image processing techniques to support automatic navigation.to support automatic navigation. This system is designed to improve robot's navigation capabilities in a dynamic environment by utilizing image processing as the main method in detecting and recognizing objects and obstacles around it.and obstacles around it. Pixy camera module is used as the main visual sensor integrated with the robot control system. Image processing techniques are applied to identify the optimal object and search for the object continuously, continuously. The test results show that the robot is capable of navigate independently with a high degree of accuracy in various environmental scenarios, environment. This implementation shows significant potential in development of autonomous robots that are more intelligent and adaptive to changes in the surrounding environment.surrounding environment.